2018
DOI: 10.1016/j.applthermaleng.2017.10.157
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of spanwise gaps in cylindrical vortex generators for conjugate heat transfer enhancement in micro-channels

Abstract: Benefits of spanwise gaps in cylindrical vortex generators for conjugate heat transfer enhancement in micro-channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…The conjugate heat transfer model and validations against previous studies of the micro-channel is presented as in [1,5,6]. Al2O3 and SiO2 nanoparticles are considered to be separated from each other and well distributed in water as a base fluid at all ranges of concentrations to offer homogeneous nanofluid.…”
Section: Analysis and Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…The conjugate heat transfer model and validations against previous studies of the micro-channel is presented as in [1,5,6]. Al2O3 and SiO2 nanoparticles are considered to be separated from each other and well distributed in water as a base fluid at all ranges of concentrations to offer homogeneous nanofluid.…”
Section: Analysis and Modellingmentioning
confidence: 99%
“…This brings to fore the need to eliminate the generated heat as it could adversely affect the electronic chip. This can be achieved in a number of ways, using air and waterbase cooled heat sinks [1][2][3][4] and the use of mini-and micro-channel heat exchangers and/or advanced fluids [1,[5][6][7]. Micro-channel design is being modified rapidly to meet the recent improvement in electronic chips and to enhance the heat transfer rate [8].…”
Section: Introductionmentioning
confidence: 99%
“…The goal of a VG is to disturb the flow in the channel to improve heat transfer performance. The disturbed flow will create vortices which can be categorised into transverse and longitudinal vortices [23,24]. A transverse vortex has its rotation axis at a right angle to the direction of flow and a longitudinal vortex has it parallel to the direction of flow [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The half-circle VG resulted in lower pressure drop compared to the quarter-circle VG. Moreover, Al-Asadi et al [23] thoroughly studied three different models of placing the VG for full span, centred and split configurations. The results showed that the centred VG offered better heat transfer improvement compared to the other two models with an optimum number of VGs (5 circular VGs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation